The third millennium dementia epidemic - Tjan, Richard (Universa Medicina, 2018)
The global dementia epidemic now and in the future is mainly caused by the steady increase in the population of older persons, where around 2 billion people will be 60 years of age and older by 2050.(1,2) As a consequence, in that yearÂ  there will be 135 million people with dementia, particularly in low- and middle-income countries where 60% of the more than 47 million cases (2015 estimate) are living now.(2)